2018
DOI: 10.1109/tasc.2017.2785388
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Analysis of the Short Model Magnets for the Nb $_{3}$Sn Low-$\beta$ Quadrupole MQXF

Abstract: During the development of MQXF, the new Nb3Sn quadrupole to be used in the LHC inner triplets for the High Luminosity upgrade, three short models were tested: MQXFS1, MQXFS3 and MQXFS5. These models differ in the use of thin or thick laminations for the iron components, in the coil design and in the superconductive strands, RRP or PIT. In the MQXF design, the azimuthal prestress is provided at room temperature by means of the bladder-key technology, and it is further increased during the cooldown by the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Initial results of the MQXFS magnets were suggesting a higher coil preload would be necessary to prevent detachment of the pole turn in the coils. To help achieve this the use of small gap between the pole key and collars was explored in the MQXFS5 [8], and for the MQXFA1 it was determined that leaving a small gap of 25-50 µm per side between collars and pole keys would allow the coils to achieve proper preload levels without increasing the stress in the shells, which was approaching engineering limits of the 7075 alloy [17]. Feeler gauges measurements confirmed that there was an average gap of 50 µm between the pole keys and collars of the final coil pack.…”
Section: ) Pole Gap Key Shimming Changementioning
confidence: 99%
See 1 more Smart Citation
“…Initial results of the MQXFS magnets were suggesting a higher coil preload would be necessary to prevent detachment of the pole turn in the coils. To help achieve this the use of small gap between the pole key and collars was explored in the MQXFS5 [8], and for the MQXFA1 it was determined that leaving a small gap of 25-50 µm per side between collars and pole keys would allow the coils to achieve proper preload levels without increasing the stress in the shells, which was approaching engineering limits of the 7075 alloy [17]. Feeler gauges measurements confirmed that there was an average gap of 50 µm between the pole keys and collars of the final coil pack.…”
Section: ) Pole Gap Key Shimming Changementioning
confidence: 99%
“…HE development of the MQXF inner triplet quadrupoles for the High Luminosity LHC upgrade has been a major effort of the LHC Accelerator Research Program (LARP) collaboration in partnership with CERN [1], [2]. Based on a series of technology development models [3]- [6] and most recently the MQXFS structures, 1.2 m magnetic length models of the same cross section [7] [8], the MQXFA structure is a 4.2 m magnetic length quadrupole with a 150 mm bore. The actual yoke length from end to end is 4.56 m long, not includ-Manuscript submitted August xx, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…MAGNET COMPARISON Fig. 6 (earlier plots and their analysis can be found in [9], [10]) and Table I show that most of the magnets have been preloaded to nominal conditions in terms of countering the electro-magnetic forces. The nominal azimuthal and axial preloads for MQXF are 120 MPa and 1.2 MN, respectively.…”
Section: Pole Imbalancementioning
confidence: 99%
“…The two different slopes of rod force (5.4 kN and 7.8 kN) during powering can be categorized based on the two different mechanical structures [11]. In [9] it is proposed that this could be due to the different modulus of thin and thick iron laminates or a different coil-collar friction coefficient. MQXFS6c is the same as MQXFS6b but after the warm up it was unloaded, azimuthally, from 13.85 mm down Fig.…”
Section: Pole Imbalancementioning
confidence: 99%
“…Overall the two independent stain gauge systems gave consistent results which were largely in agreement with calculations. More general mechanical analysis for short QXF magnets is found in [10].…”
Section: A Magnet Stress Monitoringmentioning
confidence: 99%